Central counterparties and liquidity provision in cash markets - Thomas Richter (Journal of Risk and Financial Management, 2021)
This paper investigates increased liquidity provision by market makers resulting from their ability to reduce balance sheet encumbrance through the use of central counterparties (CCPs). The introduction of the Basel III leverage rule constitutes a shock to market makers' balance sheets and thus affects their capacity to intermediate trades. Using trade-by-trade data from sovereign bond markets, we show that liquidity provision by CCP members decreased to a lesser extent following the rule change. We attribute these findings to balance sheet reductions due to the netting enabled by CCPs, thereby highlighting their importance in cash markets.
Keywords: G10; G12; G18; G21; 330; trading activity; liquidity provision; market making; central counterparties; Basel III